Pengaruh ROE, DER dan DPR Terhadap Harga Saham Pada Perusahaan Sektor Kesehatan Periode Tahun 2017-2020 - Priyo Suwono; Heni Hirawati (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Widya Gama, 2022)
Objectives - This study aims to determine the effect of Return on Equity (ROE), Debt to Equity Ratio (DER), and Dividend Payout Ratio (DPR) on stock prices with the object of research being health sector companies that have been listed on the Indonesia Stock Exchange (IDX) period year 2017-2020. Design/methodology/approach - Quantitative research using secondary data and sample determination using a purposive sampling technique. Findings - 1. Return on Equity (ROE) has no effect on stock prices. 2. Debt to Equity Ratio (DER) has a significant positive effect on stock prices. 3. Dividend Payout Ratio (DPR) has no effect on stock prices. 4. Return on Equity (ROE), Debt to Equity Ratio (DER), and Dividend Payout Ratio (DPR) together have a significant positive effect on company stock prices in the health sector. Limitations/implications – This study focuses on financial ratio analysis and does not include other factors that influence investment decisions.